How Communicative Language Enhances Student Engagement in ESL Classrooms - Dianda Putri (UPT Perpustakaan Universitas Jambi, 2025)
This review article explores how Communicative Language Teaching(CLT)improves student engagement in English as a Second Language (ESL)classrooms. The goal of this review is to support the idea that CLT is an effective teaching approach that makes students more active and motivated in learning English.CLT focuses on communication through activities like role-plays, discussions,andgroup tasks,which encourage students to use English in real-lifesituations.Research from various experts, such as Richards (1983), Savignon (2002), and Littlewood (1981), shows that CLT increases student engagement by promoting participation and improving communicative competence. However, there are some challenges in applying CLT, such as large class sizes, mixed proficiency levels, and teacher resistance. To solve these problems, training teachers, using technology, and adapting tasks to fit local cultures are recommended. The review concludes that CLT creates a more interactive and engaging classroom environment, helping students become more confident and competent in using English.